Estabelecimento de um modelo ex vivo de ferida crônica em pele porcina: uma abordagem comparativa com modelo in vitro para o estudo de biofilmes bacterianos - SantoS Filho, Anisio Silvestre Pinheiro (2019)
The chronic injury is a disabling disease closely related to aging and to chronic diseases, such as diabetes, arterial hypertension and obesity. They are also associated to the biofilms, responsible to antimicrobial resistance, persistence and progression of the clinical picture, specially of Staphylococcus aureus and Pseudomonas aeruginosa. Thus, it is important, in order to better comprehend the etiopathogeneses involved on this relation, to develop a more reliable to the in vivo conditions model. Therefore, the aim of this study was to establish an ex vivo model of chronic injuries on porcine skin to the study of S. aureus and P. aeruginosa biofilms and compare them to the in vitro model. To do so, three strains of each species were evaluated, which one of these strains was the control case (S. aureus ATCC 29213 and P. aeruginosa ATCC 27853) and the other two were clinical strains. To the ex vivo model, fragments of skin measuring 1,5 cm x 1,5 cm were disinfected with 70% alcohol and 12% NaOH. An orifice measuring 0,8 cm of diameter was made to the removal of epidermis, where the bacterial inoculum of 1,5-1,8 x 109 CFU/mL (25 µL) was placed. The in vitro biofilms were formed on polystyrene plaques, using BHI broth supplemented with 1% of the glucoses (175 µL) and bacterial inoculum of 1,5-1,8 x 109 CFU/mL (25 µL). The in vitro and ex vivo biofilms were incubated at 37 ºC each for 48, 72, 96 and 120 hours. In each period of evaluation, the CFU counting and the quantification of the matrix proteins and the counting of proteases and siderophore production were made. The ex vivo biofilms were evaluated via optical microscopy and confocal microscopy. It was observed that the CFU counting and the quantification of the matrix of S. aureus and P. aeruginosa ex vivo biofilms were significantly (P < 0,05) greater than those of in vitro biofilms, especially the ones of 48-96 hours of growing. The confocal microscopy of ex vivo biofilms have shown one significant (P < 0,05) reduction of the biomass and the thickness, for 96 hours, and a greater (P < 0,05) robustness at 72 hours of growing, to both the species. In matters of the production of virulence factors, S. aureusex vivo biofilms produced fewer siderophore and proteases than in vitro biofilms, while P. aeruginosaex vivo biofilms produced more siderophore and fewer proteases than those which have grown in vitro. The results have shown that ex vivo biofilms presented more cells and matrix and greater biomass and robustness than those which have grown in vitro, emphasizing the importance of working with ex vivo models, once it mimics better the host environment and it creates more reliable conditions to the study of chronic injuries.